Diurnal Variation of Corneal Tangent Modulus in Normal Chinese. Issue 12 (December 2016) - Hon, Ying; Wan, Kin; Chen, Guo-Zhen; Lu, Shu-Hao; Lam, David C. C.; Lam, Andrew K. C.
Abstract : Purpose: The aim of this study was to investigate the diurnal variation of corneal tangent modulus, measured using a novel corneal indentation device, in healthy Chinese subjects. Methods: The central corneal thickness (CCT), mean central corneal radius (meanK), intraocular pressure (IOP), and corneal stiffness of 25 young adults aged 21 to 25 years (23.0 ± 1.0 yrs) were measured at 3-hour intervals from 09:00 to 21:00 in the course of 1 day. Corneal tangent modulus was calculated on the basis of corneal stiffness, CCT, and meanK. Repeated-measures analyses of variance were performed to compare the diurnal changes in ocular parameters over time. Results: Significant diurnal variations were observed in CCT and IOP ( P < 0.001 and P = 0.025, respectively). Both parameters showed a decreasing trend throughout the day. MeanK and corneal stiffness did not show any significant diurnal changes ( P = 0.251 and P = 0.516, respectively). Mean corneal tangent modulus across all measurements was 0.047 ± 0.085 MPa, and its diurnal rhythm ranged from 0.469 to 0.485 MPa. The variation was nonsignificant ( P = 0.526). Conclusions: The elastic properties of the cornea in healthy Chinese subjects were stable during wake time. The present study shows that the corneal indentation device obtains stable corneal biomechanics similar to other clinical devices. Future studies investigating the differences in corneal biomechanics among patients with various ocular conditions are warranted. Abstract : Supplemental Digital Content is Available in the Text.